Efficient Ho:CaF2 laser intracavity-pumped by a Tm:LuAG laser in-band pumped at 1.6 µm. (24th July 2018) - Duan, X M; Guo, X S; Yao, B Q; Zheng, L H; Su, L B
Abstract: In this paper we demonstrate an efficient intra-cavity pumped Ho:CaF2 laser based on a tandem in-band pumping scheme for the first time. The laser diode at 1.6 µ m was employed to pump a Tm:LuAG crystal. At an incident laser diode pump power of 9.5 W, the in-band pumped Tm:LuAG laser realizes a maximum output power of 2.3 W and a slope efficiency of 33.4%. With the same incident pump power, a maximum output power of 1.5 W at 2085 nm was achieved with a slope efficiency of 24.2% in the Ho:CaF2 laser intra-cavity pumped by the Tm:LuAG laser. The beam quality factor of the Ho:CaF2 laser at the maximum output level was measured to be 1.3 and 1.2 in the horizontal and vertical directions, respectively.